2021
DOI: 10.1259/bjr.20200695
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and endovascular management of pulmonary arteriovenous malformations

Abstract: Pulmonary arteriovenous malformations (PAVM) are abnormal communication of a branch of the pulmonary artery and pulmonary vein circumventing the intervening pulmonary capillaries. This results in a right-to-left (R-L) shunt and its related manifestations, which include hampered gas exchange leading to hypoxaemia, dyspnoea, paradoxical emboli leading to stroke, cerebral abscess, myocardial infarction and pulmonary haemorrhage due to rupture of the PAVM. Endovascular transcatheter embolization of the feeding ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 56 publications
0
20
0
7
Order By: Relevance
“…Until now, there are no randomized controlled trials or reviews to compare interventional embolization and minimally invasive thoracic surgery, even Da Vinci robotic-assisted thoracoscopic surgery. Due to the great trauma and numerous intra-operative and post-operative complications of traditional open surgery, intervention with less invasive had been the first choice to treat PAVMs since the 1980s, and open surgery had only been used as a supplement to PAVMs which are not amenable to embolization or an emergency surgery to control hemorrhage [ 5 , 6 ]. With the development of minimally invasive techniques, video-assisted thoracoscopy and even Da Vinci robotic-assisted thoracoscopic surgery have been proven to be safe and feasible, which can significantly reduce the damage to patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there are no randomized controlled trials or reviews to compare interventional embolization and minimally invasive thoracic surgery, even Da Vinci robotic-assisted thoracoscopic surgery. Due to the great trauma and numerous intra-operative and post-operative complications of traditional open surgery, intervention with less invasive had been the first choice to treat PAVMs since the 1980s, and open surgery had only been used as a supplement to PAVMs which are not amenable to embolization or an emergency surgery to control hemorrhage [ 5 , 6 ]. With the development of minimally invasive techniques, video-assisted thoracoscopy and even Da Vinci robotic-assisted thoracoscopic surgery have been proven to be safe and feasible, which can significantly reduce the damage to patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intrapulmonary manifestations are as follows: dyspnea after the activity, dizziness, easy to fatigue, etc. [8][9][10] Physical examination may reveal cyanosis, clubbing fingers(toes), and chest continous murmur, etc. Some patients may only present with abnormal arterial blood gas analysis.The extrapulmonary manifestations are as follows: migraine, TIA, ischemic stroke, brain abscess, epilepsy, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may only present with abnormal arterial blood gas analysis.The extrapulmonary manifestations are as follows: migraine, TIA, ischemic stroke, brain abscess, epilepsy, etc. [8][9][10] Espejo-Herrero et al 1 reported a patient with TIA presenting with a short-term (30 min) right limb paralysis, and subsequent pulmonary arteriography showing a PAVF. Pulmonary DSA is the gold standard for the diagnosis of PAVF, which can observe the fistula size, feeding artery, draining vein and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy, pulmonary hypertension and renal impairment are relative contraindications to elective embolization procedures, although benefits may outweigh risks, particularly in the setting of life‐threatening haemoptysis 82 . Complications related to endovascular treatment include allergy to contrast agents, local puncture site complications (with common femoral vein or jugular vein as access sites), fever and pleurisy 81,91 . Complications such as coil dislodgement or stroke are not reported on a regular basis in larger series; some larger trials report no complications after embolization 81 …”
Section: Pavm Embolizationmentioning
confidence: 99%
“…82 Complications related to endovascular treatment include allergy to contrast agents, local puncture site complications (with common femoral vein or jugular vein as access sites), fever and pleurisy. 81,91 Complications such as coil dislodgement or stroke are not reported on a regular basis in larger series; some larger trials report no complications after embolization. 81 The technical success rates are usually over 80% and approaching 95% in some series.…”
Section: Embolizationmentioning
confidence: 99%